Light element variations within the different age-metallicity populations in the nucleus of the Sagittarius dwarf - Sills, Alison; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society. Letters, 2019)
ABSTRACT. The cluster M54 lies at the centre of the Sagittarius dwarf spheroidal galaxy, and therefore may be the closest example of a nuclear star cluster. Ei